Civil Law In Health Services Practice In Indonesia: Systematic Review - Tamon, Oktavian; Yuyut Prayuti (Sean Institute, 2023)
Health services are one of the efforts that can be made to improve the health status of both individuals and groups or society as a whole. In its implementation it cannot be separated from legal rules and regulations. So it is hoped that this health service practice will not go off track. The aim of this systematic review is to examine journals that explain how civil law applies to health service practices in Indonesia. This systematic review uses articles in the PubMed, Google Scholar, and ProQuest databases published in 2018-2023, getting 759 articles then reviewed using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) diagram and getting 5 articles that meet the requirements to be applied. From the results of 5 articles, it was found that civil law in health service practice includes laws that regulate protecting patient rights, doctors' legal responsibilities regarding patient lawsuits, doctors' responsibilities towards patients and maintaining patient information confidentiality. It can be concluded that civil law in health service practice has provisions that regulate the rights and obligations of doctors and health workers to patients. Civil health law is also a tool or collection of rules. Civil law is the regulation of rights, property and anything related between individuals and legal entities. So it is important for doctors and health workers to understand and carry out health services in accordance with applicable procedures and laws as well as health norms.